ASSESSMENT OF FOG AND RAIN INDUCED-ATTENUATION ON TERRESTRIAL FSO LINKS - Ajewole, M. O.; Owolawi, P. A.; Ojo, J. S.; Adetunji, R. M. (APTIKOM Journal on Computer Science and Information Technologies, 2019)
Launching into the next generation of wireless communication network (5G network) requires secure highdata rate, high speed and huge bandwidth links. With the tremendous increase in broadband users, the existingcommunication systems such as radio frequency (RF) and microwave links cannot meet up with the challenges due totheir link interference and low bandwidth. A current technology that promises such requirements and more is FreeSpace Optical (FSO) communication. The FSO basically involves the transmission of signal-modulated opticalradiation from a transmitter to a receiver through the atmosphere or outer space. It is designed to complement thetraditional fibre optical communication links. However, location-variant atmospheric channel degrades the qualityand performance of an FSO system under severe atmospheric conditions. This paper attempts to assess both fog- andrain-induced attenuation on the performance of FSO link in a terrestrial terrain using measured visibility and rainrate data at Akure, Nigeria. 5-year (2012-2016) archived visibility data and measured rain rate data of 1-minuteintegration time obtained from Nigerian Meteorological Agency (NIMET) and the Department of Physics, FederalUniversity of Technology, Akure respectively, were used to compute the fog- and rain-induced specific attenuationsusing Kruse and Carboneur models. The performance of the FSO system was analyzed through link margin by usingthe parameters of a commercial optical transceiver, Terescope 5000. Findings from this work will be useful for FSOsystem design in the area.